Effect of tera Indonesia exercise on BMI and resting pulse rate in people aged 50 years and above - Widodo, Dirga; Kinanti, Rias Gesang; Andiana, Olivia (Universitas Tanjungpura, 2024)
Changes experienced by the elderly are a decrease in physical fitness such as heart-lung and circulatory fitness. This results in the elderly getting tired easily when doing physical activity. So it takes a physical activity that produces results for the elderly with the right dose and dose. This article aims to examine the Indonesian Tera Gymnastics on BMI and pulse frequency. The method used is an experimental research model, using a one group pre-test and post-test design framework through a process before and after treatment in the form of Tera Gymnastics carried out 3 times 1 week in 4 weeks. The instrument used in collecting BMI data is measuring body weight and height. The technique of collecting assessment samples using Purposive Sampling. The sample obtained was 33 people with the research subject was COOM (Branch of Community Sports Organization) Gymnastics Tera Indonesia who participated in training at Slamet Park, Malang City. Data processed descriptively using statistical tests. The results of the analysis showed that Tera Gymnastics did not have a significant effect on reducing BMI (p = 0.281 0.05). However, there was a significant effect on the decrease in resting pulse rate before and after exercise (p = 0.000 0.05). In addition, the average pulse rate after exercise was in the light intensity category, according to the fitness level of the elderly. In conclusion, Tera Gymnastics is effective in reducing resting pulse rate, which contributes to improved cardiovascular health, although it does not significantly affect BMI.